2010
DOI: 10.1103/physrevb.82.165431
|View full text |Cite
|
Sign up to set email alerts
|

Bulk and surface energetics of crystalline lithium hydride: Benchmarks from quantum Monte Carlo and quantum chemistry

Abstract: We show how accurate benchmark values of the surface formation energy of crystalline lithium hydride can be computed by the complementary techniques of quantum Monte Carlo (QMC) and wavefunctionbased molecular quantum chemistry. To demonstrate the high accuracy of the QMC techniques, we present a detailed study of the energetics of the bulk LiH crystal, using both pseudopotential and all-electron approaches. We show that the equilibrium lattice parameter agrees with experiment to within 0.03 %, which is around… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
23
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 52 publications
1
23
0
Order By: Relevance
“…The CC and QMC values were calculated using all-electron approaches, i.e., by treating the core electrons in the same way as the valence electrons. The all-electron results indicated that core-valence correlations contributed appreciably to the overall surface energy of LiH, accounting for approximately 0.03 J/m 2 according to CC calculations [18]. However, because such calculations rely on -point-only sampling, large repeated supercells are needed.…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…The CC and QMC values were calculated using all-electron approaches, i.e., by treating the core electrons in the same way as the valence electrons. The all-electron results indicated that core-valence correlations contributed appreciably to the overall surface energy of LiH, accounting for approximately 0.03 J/m 2 according to CC calculations [18]. However, because such calculations rely on -point-only sampling, large repeated supercells are needed.…”
mentioning
confidence: 97%
“…The data for LiH are used as a benchmark because Binnie and coworkers [18] have calculated the surface energy of this material using two high-level methods: hierarchical coupled cluster (CC) [34] and quantum Monte Carlo (QMC) [35]. These methods predict surface energies of 0.434 J/m 2 and 0.44(1) J/m 2 , respectively, for LiH(001).…”
mentioning
confidence: 99%
“…For these reasons, we envisage that QMC methods will play an increasingly more relevant role in prospective DFT benchmark studies of GAM. (Actually, the DMC method has already been applied to the study of metal hydrides [228,229,287] and metal oxides [288][289][290], two important families of materials within the context of hydrogen storage and carbon capture.) It is worth noticing, however, that QMC methods are neither exempt of some important technical problems.…”
Section: Discussion and Prospective Workmentioning
confidence: 99%
“…These error cancellations, however, do not occur systematically and may depend on the specific details of GAM (e.g., see work [227] where the sign of the difference between the GGA and vdW-DF2 energies varies with the dopant species), and thus the use of standard DFT methods for modeling of carbon-based H 2 -storage materials is not recommended. Meanwhile, new quantum Monte Carlo (QMC) and RPA-DFT simulations, this time performed in periodic systems, are highly desirable for rigorously evaluating the performance of meta, hybrid, and dispersion DFT functionals (see works [152,195,[228][229][230] for examples of applications of such advanced computational methods to simulation of relevant materials). QMC and RPA-DFT calculations are also necessary for determining the relevance of many-body energy and Coulomb screening ef-fects on the present class of GAM, which so far have been systematically neglected.…”
Section: Packagementioning
confidence: 99%
“…Nowhere is this more true than in the solid state, where application of high-level quantum chemistry methods are only beginning to emerge in a recently growing field [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17]. The reason for this slow uptake is the computational cost of these methods, which generally scale as a high power of the system size, compared to the lower mean-field scaling of DFT.…”
Section: Introductionmentioning
confidence: 99%